Pengaruh Terapi ROM Aktif (Spherical Grip) Menggenggam Bola terhadap Peningkatan Kekuatan Otot Extremitas Atas pada Pasien dengan Gangguan Mobilitas Fisik Akibat Stroke: The Effect of Active ROM Therapy (Spherical Grip) Using a Ball on the Improvement of Upper Extremity Muscle Strength in Patients with Impairments - Reti Ratna Djuwita reti (MPI Press, 2024)
Introduction: This research highlights the effect of ball grasping active ROM therapy (spherical grip) on increasing upper extremity muscle strength in patients with impaired physical mobility due to stroke at Vania Hospital, Bogor, which was carried out from October 2023 to February 2024. Objectives: This research is important because researchers want to see and prove the effect of ball grasping training on increasing upper extremity muscle strength in stroke patients. Method: This research uses a quantitative approach with a One Group Pre-Post Test Design research design with data analysis using paired sample T-Test statistics. The sample in this study was 32 stroke patients undergoing treatment at Vania Hospital. Sampling used the Total Sampling technique, with research instruments using observation sheets and muscle strength scale measurements using MMT (Manual Muscle Testing). Result: With the results that before the Active ROM Grasping the Ball therapy was carried out, the muscle strength had muscle contractions (Scale 1) in 20 stroke sufferers with a frequency of 62.5%. After the Active ROM Grasping the Ball therapy, the muscle strength was greatest in the strength of being able to move the palms and fingers. - fingers (Scale 3) as many as 18 stroke sufferers with a frequency of 56.3% Conclusion: The findings indicate that Active ROM therapy using a ball (spherical grip) has a significant effect on increasing upper extremity muscle strength in stroke patients with impaired physical mobility. This therapy can be considered an effective intervention in stroke rehabilitation programs.